Effect of Amendments on Micronutrient Status, chlorophyll Content and Root Growth Parameters of Aonla (Embilica officinalis Gaertn) in Sodic Soil - Tewari, R.K.; Pandey, D.; Shukla, S.K.; Pathak, R.K. (Indian Journal of Agroforestry, 2020)
The experiment was conducted at Janta Post Graduate College, Bakewar, Etawah (U.P.) in Sodic soil having 70.63 Exchangeable Sodium Percentage (ESP), 0.78 dSm-1, Electrical Conductivity (EC) and 10.35 pH. One year old budded plants of aonla cv. Chakaiya were planted in 1.0 x 1.0 x 1.0 m size pits spaced at 8 x 8 m amended with gypsum, pyrite, usar tor masala, press mud (each at 50% GR Value) and pond sediment (complete replacement) along with control. Pits were filled uniformly with a mixture of top soil, amendments, well decomposed Farm Yard Manure (50 kg) and sand (20 kg). The results showed definite improvement in leaf micronutrient status, chlorophyll content and root growth in all the treatment over control. Pond sediment treated plants recorded maximum Zn (36.56 ppm) and Cu (8.16 ppm) in leaves followed by pyrite treated plants, whereas Fe content was maximum under pyrite (972.20 ppm) followed by pond sediment. The chlorophyll content was significantly higher than rest of the treatments, while root growth, root spread, root volume and root weight were highest in response to application of pond sediment.